English for the job market. Design and implementation of an app (offline in beta test) for the teaching of technical English (ESP) in the area of construction and wood. - Guzman Zabala, Juan Francisco
New technologies pose challenges to the foreign language teaching process, in our case, the teaching of English for Specific Purposes (ESP) at the CTCM. Therefore, we have decided to develop an application for mobile phones (smartphones) using concepts taken from “m-learning, MALL, CALL, SCRUM methodology, for the development of applications, the Task- Based Approach for foreign language teaching, and the Communicative Approach. It is expected that this application be used offline by the apprentices of the center in case they do not have a data plan on their mobile devices. The app construction process involves the implementation of various processes ranging from code design, Web architecture, icon design, technical vocabulary in English, definitions, pedagogical and playful activities, conceptual and theoretical framework, results and conclusions, just to mention a few of them. The project clearly explains its importance, the theoretical and methodological concepts that must be taken into account when using the app, a booklet with its corresponding user manual in both English and Spanish and the preliminary results obtained in the (Alpha testing) stage. Finally, predictions are made about the advantages, scope and possible limitations that may be found at the time of its implementation at the CTCM.